2019
DOI: 10.1371/journal.ppat.1007536
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from Kaposi Sarcoma-associated herpesvirus lymphoma induce long-term endothelial cell reprogramming

Abstract: Extracellular signaling is a mechanism that higher eukaryotes have evolved to facilitate organismal homeostasis. Recent years have seen an emerging interest in the role of secreted microvesicles, termed extracellular vesicles (EV) or exosomes in this signaling network. EV contents can be modified by the cell in response to stimuli, allowing them to relay information to neighboring cells, influencing their physiology. Here we show that the tumor virus Kaposi’s Sarcoma-associated herpesvirus (KSHV) hijacks this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 70 publications
(93 reference statements)
1
73
0
Order By: Relevance
“…They are rare but can spread through blood and have proven life-threatening. Kaposi’s sarcoma-associated herpesvirus (KSHV) is shown to change the microenvironment by utilizing the host-derived exosomes [ 80 ]. Epidermal growth factor receptor plays an important role in the infection of KSHV, and this is promoted by the exosomes associated with HIV [ 81 ].…”
Section: Eye Cancersmentioning
confidence: 99%
“…They are rare but can spread through blood and have proven life-threatening. Kaposi’s sarcoma-associated herpesvirus (KSHV) is shown to change the microenvironment by utilizing the host-derived exosomes [ 80 ]. Epidermal growth factor receptor plays an important role in the infection of KSHV, and this is promoted by the exosomes associated with HIV [ 81 ].…”
Section: Eye Cancersmentioning
confidence: 99%
“…Much work is still necessary to fully uncover the depth to which miRNAs influence the fate of viral RNAs and the physiological consequences of this activity. Several studies have reported functions for miRNAs far beyond this scope, especially with reports describing their incorporation into extracellular vesicles and even KSHV virions for signaling in a paracrine like manner [94,95]. With these findings in mind, several questions remain regarding what cellular and viral factors drive the expression of miRNAs and why their expression levels vary drastically between KSHV life cycle stages and tissue-derived samples.…”
Section: Rna Decaymentioning
confidence: 99%
“…Bead-based purification efficiency depends on antibody affinity, availability, and ligand density on viruses or EV surface [ 30 ]. This technique rapidly and successfully enriched and separated marker-positive EV from viruses, and other EV which did not carry the specific marker and allowed the identification of exosome enclosed RNAs and proteins [ 32 , 33 , 36 , 46 , 47 ].…”
Section: How Do Rnas Co-purify With Viruses and Ev By Different Pumentioning
confidence: 99%
“…Despite many studies, the mechanisms for incorporating mRNA and non-coding RNA into virions remains incompletely understood and is subject to intense debate. The biological roles that the EV-mediated transfer of RNAs plays in viral pathogenesis are just beginning to emerge, for example in human herpesviruses [ 36 , 46 , 74 , 75 , 76 ]. Insights derived from the virus-mediated transfer of intact RNAs could, therefore, provide an example for EV-mediated transfer of functional RNA.…”
Section: Do Dna Viruses Package Rnas In Virus Particles?mentioning
confidence: 99%
See 1 more Smart Citation